Mid-Term Appraisal for the Ninth Plan 1997-2002 - Planning Commission (Planning Commission, 1997)
The approved Ninth Plan (1997-2002) outlay of Mizoram Is Rs.161851 lakhs. There is an increase of about 52% over the total Eighth Plan expenditure which was Rs. 106233 lakhs-at current prices. The sector wise percentage distribution of 9th Plan outlay is as follows :(1) Agriculture & Allied activities 6.96% (2) Rural Development 14.54% (3) Special Area Programme 0.01%. (4) Irrigation and Food Control 1.12% (5) Energy 13.85% (6) Industry & Minerals 4.26% (7) Transport 16.82% (8) Science, Technology & Environment 0.20% (9) General Economic Services 5.23% (10) Social Services 32.69% (11) General Services 1.81% (12) Forestry & Wildlife 2.51%.
Government of Mizoram